2017
DOI: 10.4274/jpr.22932
|View full text |Cite
|
Sign up to set email alerts
|

National Newborn Screening Tests Carried Out with Heel Lance and Their Importance

Abstract: Ge liş ta ri hi/Re cei ved: 16.02.2016 Ka bul ta ri hi/Ac cep ted: 25.04.2016

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 3 publications
0
6
0
2
Order By: Relevance
“…Neonatal tarama programları ve kapsamları ülkelere göre farklılık göstermektedir (3) . Ülkemizde ise 2006 yılında fenilketonüri (FKÜ) ve konjenital hipotroidi taraması ile başlayan neonatal tarama programlarına 2008 yılında biyotinidaz eksikliği paneli, 2015 yılında ise Kistik fibrozis taraması eklenmiştir (12) . Hastalarımızdan yalnızca birisine neonatal tarama programı kapsamında tanı konuldu.…”
Section: Discussionunclassified
“…Neonatal tarama programları ve kapsamları ülkelere göre farklılık göstermektedir (3) . Ülkemizde ise 2006 yılında fenilketonüri (FKÜ) ve konjenital hipotroidi taraması ile başlayan neonatal tarama programlarına 2008 yılında biyotinidaz eksikliği paneli, 2015 yılında ise Kistik fibrozis taraması eklenmiştir (12) . Hastalarımızdan yalnızca birisine neonatal tarama programı kapsamında tanı konuldu.…”
Section: Discussionunclassified
“…One of the recently adopted methods used to reduce pain during neonatal heel stick procedures is heel warming (Cong, 2015;Zhu et al, 2015). Heel warming increases vascularity by causing vasodilatation in the region and facilitates sampling by accelerating blood flow (Icke & Genc, 2016;Janes, Pinelli, Landry, Downey, & Paes, 2002). It is also reported that vasodilatation provided by heel warming influenced the duration of the bleeding process and the crying period of the newborn (Cong, 2015;Zhu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…17,20,21) Therefore, a remarkable feature is the musty odor caused by increased levels of phenylpyruvic acid, phenylacetic acid, and phenyllactic acid in the body fluids and urine of these patients. 17,22) When PKU is not treated early, it can cause behavioral problems, psychiatric symptoms, motor disorders, seizures, an eczematous rash, and irreversible intellectual disability. 1,23,24) Links have also been established between high Phe levels and epigenetic alterations in gene expression patterns in the brain, disrupted myelin production, impaired cerebral glucose metabolism (as seen on positron emission tomography imaging), the accumulation of amyloid plaque-like fibrils, and increased oxidative stress.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%